On the incompatibility of ‘Western’ and Aboriginal views of Restorative Justice in Canada: a claim based on an understanding of the Cree justice - Barmaki, Reza (Contemporary justice review, 2022)
‘Restorative justice’ (RJ) has been a popular notion in Canada. A common belief has been that ‘‘western approaches’ to RJ are compatible with that of Canada’s Aboriginals. I hold a different position. I argue that the religious beliefs of Canada’s Aboriginals are basic to their understanding of RJ. As such, their view of RJ is essentially incompatible with western approaches, which are secular. Any similarity between the two is only an apparent one produced by the indiscriminate uses of similar terms such as ‘holistic’, ‘healing’ or ‘restoration’. I support my argument by providing an account of Canada’s largest Aboriginal group’s view of RJ: the Cree. I demonstrate that it is based on certain religious principles that are absent from western approaches to RJ. As such, it is fundamentally incompatible with secular western approaches to RJ in Canada. These religious principles, basically and broadly speaking, are shared by all Aboriginal groups in Canada.